A sequential subspace method for blind identification of general FIR MIMO channels - Senjian An; Manton, J.H.; Yingbo Hua (IEEE transactions on signal processing, 2005)
This correspondence addresses the problem of blindly identifying multiple input multiple output (MIMO) finite impulse response (FIR) channels without the conventional assumption of identical column degrees. A subspace-based algorithm is developed that identifies the channel's columns sequentially from the lowest degree columns to the highest degree ones. Compared with the previous generalized subspace method by Gorokhov and Loubaton (1997), the new method is simpler and more accurate.